Desarrollo del pensamiento crítico a través del trabajo colaborativo: una necesidad en la práctica docente en época de pandemia (2021)
The objective of this research is to understand from the mediation of collaborative work, with teachers of 4th grade of the IED ROVIDEAN the perspectives necessary for the development of critical thinking of students, in this way, a qualitative methodology of action research type was used, where the participants were 5 teachers of grade 4 of the institution selected through a convenience sampling. The results show that in the institution there is no reflection or evaluation of the pedagogical work, in addition, there are strategies to work on critical thinking, but these are minimal, because the institutional curriculum is not focused on this, finally, teachers consider that the project allowed them to broaden both practical and theoretical perspectives on the importance of collaborative work in the development of critical thinking, being important research for all members of the community.